مسائل العول الملقبة في المواريث: دراسة مقارنة - سليمان، نشوان زكى (جامعة كركوك - كلية القانون والعلوم السياسية, 2021)
يذهب غالبية الفقه الإسلامي إلى الأخذ بأحكام العول صراحة عند تزاحم الورثة من أصحاب الفروض في المسألة الإرثية التي يترتب عليها زيادة في سهام فروضهم عن أصل المسألة، وذلك لما يحققه العول من عدالة منصفة لجميع أصحاب الفروض حينما يدخل النقص على سهامهم جميعا بنسبة فروضهم، بينما أنكر العول ابن عباس رضي الله عنه ومن تبعه من الفقهاء المسلمين ولم يعملوا به مستدلين بظاهر آيات المواريث، وبأن التركة إذا تعلقت بها حقوق لا تفي بالتركة، وضاقت الفروض قدم الأقوى منها فالأقوى، كالتجهيز والدين والوصية، والميراث عندهم لا يخرج عن هذه القاعدة، لأن أصحاب الفروض الأقوى في نظرهم التي لا ترث بالتعصيب بحال كالأم والزوجين، ويقدمون على البنات والأخوات من الأم على الأخوات من الأبوين أو من الأب، وجعل الباقي من سهامهم لهن. وقد أخذت غالبية القوانين العربية للأحوال الشخصية ومنها القوانين محل الدراسة بأحكام العول متفقة مع ما ذهب إليه جمهور الفقهاء في قسمة مسائل العول الملقبة، إلا أن مشرعي القوانين محل الدراسة لم تنص على غالبية المسائل الملقبة في العول، إنما اكتفت بالحكم العام للعول، باعتبار أن مسائل العول من مسائل الميراث التطبيقية الحسابية في قسمة التركات، إلا أنها نصت على بعض مسائل العول الملقبة وكان من جملة هذه المسائل الإرثية مسألتي المباهلة والمنبرية." The majority of Islamic jurisprudence goes to explicitly adopting the provisions of the dependency when the heirs of the hypotheses compete in the inheritance issue that results in an increase in the shares of their assumptions from the original issue, and this is due to the fact that the dependence achieves fair justice for all the owners of the assumptions when the deficiency falls on all their shares in proportion to their homework, while denied Al-Awl Ibn Abbas, may God be pleased with him, and those who followed him from among the Muslim jurists and did not act upon it, arguing with the apparent meaning of the verses of inheritance, and that if the inheritance is attached to rights that do not meet the inheritance, and the obligations are narrowed, the stronger and the stronger, such as preparation, debt and the will, and the inheritance with them does not deviate from this rule, because the owners of In their view, the strongest obligations that are not inherited by hardship in any case, such as the mother and the spouses, and they give precedence to daughters and sisters from the mother over sisters from the parents or from the father, and make the rest of their arrows for them. The majority of the Arab personal status laws, including the laws under study, have taken the provisions of the dependency in agreement with the view of the majority of jurists in dividing the issues of reliance. Reliance is one of the applied arithmetic inheritance issues in the division of estates, but it stipulated some issues of nicknamed trust and among these issues of inheritance were the issues of Al-Mubahala and Al-Minbariya."
Keywords: الشريعة الإسلامية -- الفقه الإسلامي -- الفقهاء المسلمين -- الخلاف الفقهي